Rotator: o livro infantil digital, uma nova forma de criar narrativas visuais - Cátia Soares Vidinhas (2015)
The evolution of media and their convergence not only have provided technological development, but also a rich contribution in the way contents are conceived and transmitted. A sector in which this process has had great impact is publishing; in this field the progressive technological advance has helped defining the book as object and content. The new features that have come with mobile devices open new possibilities in the way in which stories are told and in the production of narratives, bringing new challenges for the illustrator as creator of the visual narrative. Within this context we produce a practical project, titled Rotator, based on the creation of the same narrative for a printed and a digital children book so that the two products are complementary but completely independent from one another. All along the study the focus will be on the role of the illustrator and the new expertise it will have to take charge of.